The Virtual Morris Water Task in 64 Patients With Bilateral Vestibulopathy and the Impact of Hearing Status - Dobbels, Bieke; Mertens, Griet; Gilles, Annick; Moyaert, Julie; van de Berg, Raymond; Fransen, Erik; Van de Heyning, Paul; Van Rompaey, Vincent (Frontiers in Neurology, 2020)
BACKGROUND: Previous studies have demonstrated spatial cognitive deficits in patients with bilateral vestibulopathy (BVP). However, BVP patients frequently present with a concomitant sensorineural hearing loss, which is a well-established risk factor of cognitive impairment and incident dementia. Nonetheless, previous research on spatial cognitive deficits in BVP patients have not taken hearing status into account. OBJECTIVE: To compare spatial cognition of BVP patients to healthy controls, with analyses adjusting for hearing status. METHODS: Spatial cognition was assessed in 64 BVP patients and 46 healthy controls (HC) by use of the Virtual Morris Water Task (VMWT). All statistical analyses were adjusted for hearing (dys)function, sex, age, education and computer use. RESULTS: Overall, patients with BVP performed worse on all outcome measures of the VMWT. However, these differences between BVP patients and healthy controls were not statistically significant. Nonetheless, a statistic significant link between sensorineural hearing loss and spatial cognition was observed. The worse the hearing, the longer subjects took to reach the hidden platform in the VMWT. Furthermore, the worse the hearing, less time was spent by the subjects in the correct platform quadrant during the probe trial of the VMWT. CONCLUSION In this study, no difference was found regarding spatial cognition between BVP patients and healthy controls. However, a statistically significant link was observed between sensorineural hearing loss and spatial cognition.